The Relationship between Sitting Height with VO2max and Muscular Endurance in Junior Taekwondo Athletes - Karimullah, Aldi; Atmaka, Dominikus Raditya (JSES : Journal of Sport and Exercise Science, 2025)
Purpose: This study aims to analyze the relationships among sitting height, aerobic capacity (VO2max), and muscular endurance in junior taekwondo athletes. Materials and Methods: This study used an observational, cross-sectional research design. A total of 31 junior taekwondo athletes aged 10–17 years participated in this study (20 females and 11 males). This study conducted anthropometric tests (weight, height, and sitting height) and physical tests to assess muscular endurance and maximal oxygen uptake (VO2max). Muscular endurance was measured using a push-up test, while VO2max was measured using the Multistage Fitness Test (MFT) or beep test. Result: The study found a significant relationship between sitting height and VO2max (95% CI = 34.16–39.57; r = 0.405; p = 0.024). This relationship indicates that taller junior taekwondo athletes have higher VO2max values. Meanwhile, the analysis of the relationship between sitting height and muscular endurance showed no significant association (95% CI = 24.05 – 28.26; r = 0.114; p = 0.543). Conclusion: This study concludes that greater sitting height is associated with better VO2max capacity among junior taekwondo athletes. However, sitting height does not have a significant relationship with muscular endurance. These findings suggest that sitting height is a supporting factor in the development of aerobic capacity in this population. In practical terms, the results of this study can serve as recommendations for identifying and developing talent in young athletes.